The moral attitudes of UK youth: bringing morality back to the sociology of education. Issue 7 (9th July 2020) - Baker, Will
Abstract: This paper argues that the sociology of education would benefit from greater integration with social scientific research focused on morality. This body of research offers a rich set of resources that can illuminate and extend many of the sociology of education's intellectual concerns. In support of this argument, the paper draws on data from Millennium Cohort Study in the UK to empirically examine how a wide range of socio-demographic characteristics are related to young people's moral attitudes. The analysis focuses on the extent to which adolescents state that a range of actions are wrong. In doing so, the paper makes an important contribution to studying the moral lives of young people.